Criminal Liability For The Perpetrator Of Sexual Perversion Of The Corpse - Yurista Prawitasari, Nining; Kesumojati, Rad Cloud Dirgantoro (Journal of Law, Politic and Humanities, 2025)
This study discusses necrophilia as one of the deviations of sexual orientation that has not been regulated in the Criminal Code (KUHP). Although Article 271 of the Penal Code covers the regulation of corpses, excavation or demolition of tombs, retrieval, removal and transportation of bodies, and uncivilized treatment of bodies, the act of rape of bodies still does not have clear regulations. This situation creates a legal vacuum that poses new challenges, especially since necrophilia is often seen as a form of the disease. The question arises as to how legal liability can be imposed on the perpetrator in this context. The purpose of this study is to understand the regulation and form of criminal responsibility for the perpetrators of necrophilia in the context of the crime of rape of the corpse. The method used in this study is normative legal research with a legislative approach to discuss related legal issues. The results showed that criminal liability for individuals with necrophilia in the criminal act of rape of a corpse is not yet expressly provided for in the new criminal code. In the context of criminal acts, this is stipulated in Article 271 of Law Number 1 of 2023 (KUHP), while from the perspective of criminal acts rape is regulated in Article 415 of the Criminal Code. In addition, crimes against the body are also regulated in Article 415 as well as Article 269 and Article 270 of the new criminal code.